Тема Трипільської культури у сучасному «праісторичному» міфотворенні - Відейко, М.Ю. (Археологія, 2005)
Далеке минуле, зокрема трипільська культура, є ще й джерелом для міфології. Це явище — цілком закономірне. Тисячоліттями міфи творилися в народній свідомості. Нині ми спостерігаємо, як до раніше таємничого процесу міфотворчості долучилися конкретні люди, імена яких стають відомими, а їхня «творчість» знаходить багатьох прихильників. Міфи завжди лишаються яскравою поетичною конструкцією, яка твориться та функціонує за власними правилами. Історія, у тому числі археологія, як наукова дисципліна із властивими їй методами і засобами пізнання постачає людству факти про його минуле. Проте вибір між міфом та історією може і має бути свідомим, як і розуміння можливих наслідків та власної відповідальності за зроблений вибір.
На ранніх стадіях розвитку людського суспільства наука, магія, релігія, суспільно-економічна сфера ще не були розмежованими. Тому в часи існування трипільської культури правитель, жрець, маг і науковець поєднувалися в одній особі. У сучасному світі, принаймні у світі науки, жерці, шамани, пророки втратили своє первісне значення, а їхні проповіді, якими б вражаючими вони не виглядали, у сучасному храмі Науки є недоречними. У науковців вони викликають, у кращому разі, лише подив. Тим більше дивують заклики новітніх «пророків», які люблять згадувати про свої наукові ступені, повернутися до «нерозділеного знання» і міфу, якими пропонують замінити науку. Далекое прошлое, в том числе трипольская археологическая культура, сегодня стало источником для создания исторических мифов. Такое явление вполне закономерно. Тысячелетиями мифы создавались в народном сознании. Сегодня мы наблюдаем, как к этому, ранее таинственному, процессу приобщились конкретные авторы, имена которых становятся известными, и они приобритают тысячи сторонников. Мифы, однако, всегда остаются яркой поэтической конструкцией, живущей по своим законам. История и археология — научные дисциплины со специфическими методами познания, поставляющие факты о прошлом и предлагающие их интерпретацию. В каждом случае выбор между историей и мифом может и должен быть сознательным, равно как и понимание последствий, а также ответственности за такой выбор.
На примере произведений Ю.А. Шилова; А.И. Асова, М.Ю. Коновалова и П.В. Ильина; О.А. Билоусько; П. Паламарчука и И. Андриевского мы можем ознакомиться с созданными по законам мифотворчества альтернативными научному видению картинами прошлого. При этом авторы исходят не из фактов, а из заранее заданной идеи — «Божественной Аратты», Гипербореи, положивших, по их мнению, начало мировой цивилизации. Авторы не утруждают себя доказательствами, зачастую просто выдумывая их. Трипольская культура, будучи достаточно ярким, «раскрученным», но в то же время малоизвестным широкой публике феноменом, послужила благодатным «строительным материалом» для «альтернативных» версий истории Украины. Созданные таким образом концепции не выдерживают научной апробации, поскольку рассчитаны на проповедь перед сторонниками, жаждущими понятных и красивых сказок.
Наметившиеся тенденции внедрения исторических мифов в систему среднего и высшего образования приняли в последние годы угрожающий характер. В данном случае речь идет о престиже Украины как цивилизованного европейского государства, поскольку в XIX—XX вв. аналогичные по характеру и содержанию исторические мифы не раз становились основой идеологии (и вытекающих из нее действий) агрессивных тоталитарных режимов. Наука может рассматривать подобные произведения разве что в качестве предмета ее, науки, изучения — как определенное проявление общественного сознания. Distant past, including Trypillya archaeological culture, has become a source for historical myths. This phenomenon is quite natural. For many millennia the myths have been created in the people’s minds. Nowadays we can observe individual authors joining this previously mysterious process, their names becoming well-known, and their ideas gaining support of the thousands. The myths, however, always remain vivid and poetic structures living by their own laws.
History and archaeology are branches of science possessing specific methods of cognition, supplying facts about the past, and proposing their interpretation. In each case the choice between the history and the myth can and should be conscious. The same pertains to awareness of the consequences and responsibility for this choice.
By the example of publications by Yu.O. Shilov, O.I. Asov, M.Yu. Konovalov, and P.V. Iljin; O.A. Bilous’ko; P. Palamarchuk and I. Andrievskiy we can get acquainted with pictures of the past are alternative to the science-based vision and created by the laws of myth-making. In addition, the authors proceed not from the facts, but from predetermined concept of «Divine Aratta», Hyperborea, which, in their opinion, lay at the beginning of the world civilization. At the same time they do not take the trouble to prove anything, often they simply make the evidence up. The Trypillya culture, being rather a bright, «promoted», but still little-known to the general public phenomenon, has served as a beneficial «building material», a reference point for the «alternative» versions of the Ukrainian history. The concepts created this way cannot stand the scientific tests, since they are intended to be propagated among those adherents who crave for plain and pictorial tales.
It should be noted that the tendency taking shape towards introduction of the historical myths into the system of secondary and higher education has become menacing during the recent years. In this case we deal with the problem of prestige of Ukraine as a civilized European nation, because in XIX—XX cc. the historical myths analogous in character and intention had become the background for ideology (and actions resulting from such ideology) of aggressive, totalitarian regimes. The science can obcerve related to the works of the kind only as an object of its study as certain manifestation of public conscience.